Implementation of Restorative Justice in Theft Cases (Case Study LP/B/14/VII/SPKT) - Clara Camelia Santhia; Audrey Adellawati; Dadan Taufik Fathurohman; Diky Dikrurahman (Interdiciplinary Journal and Hummanity (INJURITY), 2025)
Restorative Justice (RJ) is a non-litigation approach to resolving criminal cases that focuses on repairing the harm caused by the crime while fostering reconciliation between the victim and perpetrator. This study examines the implementation of RJ in a theft case under Article 363 of the Criminal Code in Cirebon in 2024. The purpose of this research is to evaluate how the police utilized RJ to address the theft and prioritize the rights of the victims while holding the perpetrators accountable. Using an empirical juridical method, this study analyzes the application of RJ through interviews conducted at the Kedawung Police Station, examining both legal frameworks and practical application. The results indicate that RJ offers an effective, faster, and more cost-efficient resolution for cases like petty theft, promoting victim recovery and perpetrator accountability. The case was successfully resolved when the perpetrator agreed to compensate for the stolen goods and return the victim’s losses through a family-based agreement, fulfilling both material and formal requirements as stipulated in the National Police Regulation No. 8/2021. The study concludes that RJ can be a progressive alternative for resolving criminal cases, though challenges such as community resistance and the need for law enforcement training remain potential barriers to its broader application.